CLIMATE CHANGE AND CHOLERA TRANSMISSION IN NIGERIA: A SCOPING REVIEW OF DRIVERS, PATTERNS AND CONTROL STRATEGIES - Gabo Simon; Gabo Uchenna; Adamu Ishaku Akyala; Abah Michael Idoko (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Nigeria is endemic for cholera, with recurrent outbreaks affecting multiple states. Climate is increasingly recognized as a driver of cholera transmission through effects on rainfall, temperature and flooding. This scoping review aimed to map the evidence on climate drivers of cholera transmission in Nigeria, describe epidemiological patterns, and identify implications for control strategies. We conducted a scoping review following the Arksey and O’Malley framework and the PRISMA extension for Scoping Reviews (PRISMA-ScR). We searched PubMed, Scopus and Web of Science for studies published from January 2000 to November 2024 examining climate–cholera relationships in Nigeria, supplemented by hand-searching of reference lists. Two reviewers independently screened titles/abstracts and full texts; disagreements were resolved by discussion or a third reviewer. Data were charted on study characteristics, climate drivers examined, epidemiological findings, and recommended control strategies, and synthesised narratively. Of 187 records identified, 32 studies met the inclusion criteria after de-duplication and full-text review. Rainfall variability was the most frequently examined driver (81% of studies), followed by temperature (56%) and flooding (44%). Most studies (72%) reported a positive association between heavy rainfall and cholera outbreaks; temperature findings were inconsistent across studies. The rainy season (April–October) was consistently identified as the period of highest cholera risk, with outbreaks typically peaking in June–August. Northern states, including Kano, Bauchi and Katsina, and the Federal Capital Territory were most frequently reported as high-burden areas. Recommended control strategies included strengthened surveillance and early warning, improved water and sanitation infrastructure, oral cholera vaccination, community engagement, and climate-informed public health planning. Available evidence consistently links rainfall variability and flooding to cholera outbreaks in Nigeria, while the role of temperature remains unclear, likely reflecting seasonal confounding between temperature and rainfall. Priority gaps include long-term, higher-resolution time-series analyses, evaluations of climate-responsive interventions, and better integration of climate and health surveillance data — all of which are needed to strengthen predictive, seasonally targeted cholera control in Nigeria.